The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1104/pp.120.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Hydrogen and Oxygen Isotopes in Leaf Water Confirm the Craig-Gordon Model under Wide-Ranging Environmental Conditions1

Abstract: The Craig-Gordon evaporative enrichment model of the hydrogen (␦D) and oxygen (␦ 18 O) isotopes of water was tested in a controlled-environment gas exchange cuvette over a wide range (400‰ ␦D and 40‰ ␦ 18 O) of leaf waters. (Throughout this paper we use the term "leaf water" to describe the site of evaporation, which should not be confused with "bulk leaf water" a term used exclusively for uncorrected measurements obtained from whole leaf water extractions.) Regardless of how the isotopic composition of leaf w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
233
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(246 citation statements)
references
References 36 publications
10
233
0
3
Order By: Relevance
“…There have been conflicting reports on the existence of such a relationship. Wang et al (1998) and Roden and Ehleringer (1999) observed no clear dependency of ⌬ C Ϫ ⌬ lw, bulk on E, with the former study based on a collection of 90 plant species grown under the same climatic conditions. The positive relationship between ⌬ C Ϫ ⌬ lw, bulk and E, illustrated by Wang and Yakir (2000) and Gillon and Yakir (2000), appears to be in agreement with the Péclet model but may well collapse after normalization against ⌬ C .…”
Section: Lower Enrichment Of Bulk Leaf Water Arising From Péclet Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been conflicting reports on the existence of such a relationship. Wang et al (1998) and Roden and Ehleringer (1999) observed no clear dependency of ⌬ C Ϫ ⌬ lw, bulk on E, with the former study based on a collection of 90 plant species grown under the same climatic conditions. The positive relationship between ⌬ C Ϫ ⌬ lw, bulk and E, illustrated by Wang and Yakir (2000) and Gillon and Yakir (2000), appears to be in agreement with the Péclet model but may well collapse after normalization against ⌬ C .…”
Section: Lower Enrichment Of Bulk Leaf Water Arising From Péclet Effectmentioning
confidence: 99%
“…Direct and indirect leaf water measurements supporting the different leaf water models have been reported: Craig-Gordon model (Roden and Ehleringer, 1999), Péclet model (Walker et al, 1989;Flanagan et al, 1991b;Barbour et al, 2000), and string-of-lakes model (Yakir, 1992;Wang and Yakir, 1995;Ehleringer, 2000, 2002). Given the importance of leaf water modeling to studies of plant-environment interactions, there is a pressing need to reconcile these apparently disparate results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O are enriched at the sites of evaporation (Craig and Gordon, 1965;Yakir et al, 1989;Barbour et al, 2000), the location of those sites affects the mixing of isotopically enriched water with xylem water and, thus, bulk leaf enrichment (Yakir et al, 1990;Roden and Ehleringer, 1999;Farquhar and Gan, 2003). (6) The location of the evaporating sites determines the extent to which the diffusion pathways for CO 2 and water vapor overlap, which, in turn, affects the interpretation of correlations between K leaf and mesophyll conductance to CO 2 (g m ; Flexas et al, 2013;Tomás et al, 2013), as well as (7) the opportunity for diffusive interference between water vapor and CO 2 (reflected in the ternary corrections for gas-exchange calculations; Farquhar and Cernusak, 2012).…”
mentioning
confidence: 99%
“…Through a series of known fractionation events, d 18 O (and d 2 H) variation derived from hydrologic inputs is incorporated into the organic matter that makes up tree rings (Yapp and Epstein 1982;White et al 1994;Roden and Ehleringer 1999b;Roden et al 2000;Treydte et al 2006;Gessler et al 2009). Tree-ring cellulose d 18 O values can be modified by variation in atmospheric humidity and the unique isotope values it possesses, by vapor pressure deficit and therefore the magnitude of leaf evaporative enrichment associated with transpiration (Edwards and Fritz 1986;Roden and Ehleringer 1999a;Wright and Leavitt 2006;Kahmen et al 2008), by variation in source water (Wright et al 1999;Roden andEhleringer 1999b, 2007) and by post-photosynthetic but pre-biosynthetic factors shown to dampen the original isotope values of sucrose made at the leaf-level before it becomes incorporated into tree-ring cellulose (Brandes et al 2006). Carbon isotope ratios (d 13 C) in tree-ring cellulose have been used to study historical variations in plant water status, temperature, solar radiation and vapor pressure deficit (Saurer et al 1995;Stewart et al 1995;Hemming et al 1998;Schleser et al 1999;Barbour et al 2002;Leavitt et al 2002;Young et al 2010).…”
Section: Introductionmentioning
confidence: 99%